Screening of highly effective mixed natural antioxidants to improve the oxidative stability of microalgal DHA-rich oil. Issue 9 (27th January 2021) - Yin, Fengwei; Sun, Xiaolong; Zheng, Weilong; Luo, Xi; Zhang, Yingying; Yin, Longfei; Jia, Qiang; Fu, Yongqian
Abstract : Antioxidants with synergistic effect were screened and optimized by RSM. The final natural antioxidant mixture can be actually applied in micrialgal DHA-rich oil, helping to enhance the antioxidant ability of DHA oil and extend its shelf life. Abstract : Docosahexaenoic acid (DHA)-rich oil sourced from microalgae can easily become oxidized. The objective of this work was to screen the optimal natural antioxidant mixture for protecting DHA-rich oil. Different natural antioxidants, encompassing tea polyphenols, natural vitamin E, rosemary extract, licorice root antioxidant, ascorbyl palmitate and lecithin were tested individually and in combination in an accelerated oxidation process. Three antioxidants namely natural vitamin E, rosemary extract and ascorbyl palmitate with synergistic effects were chosen, and their concentrations were further optimized using response-surface methodology. The highest antioxidants activity of 16.1740 was obtained with a combination of 0.0224% vitamin E, 0.0259% rosemary extract and 0.0166% ascorbyl palmitate, which prolonged the time until oxidation induction to 20.21 days. The mixed natural antioxidants showed a similar antioxidant effect to 0.02% tert -butylhydroquinone and was better than 0.02% butylated hydroxyanisole. These data indicate that the mixed natural antioxidants optimized in this work can be directly applied in the protection of commercial microalgal DHA-rich oil.